Language Skills and Stock Market Participation: Evidence From Immigrants - Gan, Xu; Song, Frank M; Zhou, Yang (My University, 2022)
Do language skills affect investment decisions? This article addresses this question by identifying the effect of English proficiency on the stock market participation of immigrants in the United States and Australia. To establish causality, we construct an instrumental variable for English proficiency by exploiting the phenomenon that younger children acquire languages more easily than older children. We find that English proficiency has a significant positive effect on stock ownership among immigrants in both countries. Moreover, we provide evidence that a reduction in information costs and an increase in trust may serve as the mechanisms underlying the language ability effect.
Journal of Financial and Quantitative Analysis
Keywords: Income, wealth and finances; Migration and settlement